Mulheres em processo de separação: um estudo sobre o partir ou permanecer em um relacionamento violento - Ellio, Daniela Luciana de Faria (Universidade Federal de São Carlos, 2018)
The phenomenon of violence has been considered a public health problem by WHO since 1996. In the scope of violence against women, intimate relationships are shown as one of the most common contexts for the occurrence of this phenomenon, characterized here, as violence between intimate partners ( Intimate Partner Violence - VPI). Knowing that most victims of IPV are women and that many of them are mothers, children can also be exposed to violence and both suffer from its consequences. Faced with this scenario, the separation can become a long and exhaustive process, guided by risk and protection factors, in which the woman needs to overcome myths and social beliefs to make the decision to leave or remain in the violent relationship. Thus, this study aimed to: analyze the narrative of women about their motivations in the decision to continue or interrupt this type of relationship, paying special attention to the separation process. Data collection was carried out in person and online through an individual interview lasting one hour. The interview was guided by the Interview Guide adapted from Williams (2010) and, in addition, the Conflict Tactics Scale (CTS-2) was applied for a standardized measurement of the extent of aggression. All participants reported having suffered psychological violence and nine went through episodes of physical violence, seven of whom had their children exposed to violence. All were separated at the time of the interview, however, two of them would have liked to have continued with the relationship and, in these cases, the decision to separate came from the partner. The data in this study can bring contributions not only to academic research, but also to professionals in the protection network and community, serving as a material to aid in understanding the vicissitudes of separation.
Women in the process of separation: a study on leaving or remaining in a violent relationship
Keywords: violência entre parceiros íntimos; separação; mães; exposição à violência; criança; intimate partner violence; mother; exposure to violence; children; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA